Regenerative Endodontics. (September 2017) - Feigin, Kristina; Shope, Bonnie
Regenerative endodontics has been defined as "biologically based procedure designed to replace damaged structures, including dentin and root structures, as well as cells of the pulp–dentin complex." This is an exciting and rapidly evolving field of human endodontics for the treatment of immature permanent teeth with infected root canal systems. These procedures have shown to be able not only to resolve pain and apical periodontitis but continued root development, thus increasing the thickness and strength of the previously thin and fracture-prone roots. In the last decade, over 80 case reports, numerous animal studies, and series of regenerative endodontic cases have been published. However, even with multiple successful case reports, there are still some remaining questions regarding terminology, patient selection, and procedural details. Regenerative endodontics provides the hope of converting a nonvital tooth into vital one once again.